First, do no harm : the role and responsibility of Canada as a destination country in South-North migration - Dawson, Laura Ritchie (The Centre for International Governance Innovation WaterlooCA, 2008)
Examines the role and responsibility of migrant-receiving states, and constructs a framework of intervention areas for Canada from work conducted in other developed countries. Expresses concern that wealthy, migrant-receiving countries are impeding their own overseas development efforts through migration-related policies that are contradictory or incoherent. Presents reasons for Canada to reverse this trend and embark on a new development partnership in its future relations with Caricom States.